Optimization of process parameters for rectangular cup deep drawing by the Taguchi method and genetic algorithm - Sener, Bora; Kurtaran, Hasan (CARL HANSER VERLAG, 2016)
This article presents the optimization of process parameters in reducing the risk of failure due to wrinkling and fracture in deep drawing of a rectangular cup. Blank holder force, friction coefficient, punch radius and initial blank shape were chosen as design parameters. Wrinkling and fracture criteria were used as objective functions. Two-stage optimization approach was used. In the first stage optimization, optimum blank shape was determined using the Taguchi optimization method. In the second stage optimization, optimum parameter values were determined for the selected blank shape by the first stage optimization using genetic algorithm. In the second stage of optimization, response surface models based on 3-level full factorial design of experiments were constructed. Finite element simulation results were used for creating response surface models. Parameters obtained from optimization study were confirmed by conducting deep drawing simulations using commercial code DYNAFORM 5.9.2. Optimum results showed that proposed optimization methodology can solve wrinkling and fracture problems in the sheet metal forming process.
Keywords: Rectangular cup deep drawing; wrinkling; fracture; Taguchi method; genetic algorithm; MULTI-OBJECTIVE OPTIMIZATION; PROCESS DESIGN; SHEET; FRICTION; Materials Science